TRANSNATIONAL ECONOMIC COOPERATION IN BORDER TERRITORIES: OPPORTUNITIES AND CHALLENGES - Melyana R Pugu; Erwin; Jeferson Siahaan; Mohd Syahrin (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
Transnational economic cooperation is a process of cooperation between countries in order to increase global economic growth and development. Transnational economic cooperation can take many forms, such as free trade agreements, investment agreements, and regional integration agreements. Transnational economic cooperation has an important role in maximizing infrastructure development. In fact, infrastructure development can be accelerated if all parties collaborate closely. The economy taking place in border areas must be controlled with various profitable policies, both for producers, consumers and distributors. The government's main role in encouraging opportunities for transnational economic cooperation is to control the economy with various economic policies to make its citizens prosperous. Each form of cooperation has the same goal, namely to facilitate transnational business activities and also accelerate the process of trade liberalization. This article employs a form of literature review that includes hypotheses pertaining to the issue under investigation. This research discusses transnational economic cooperation, opportunities for transnational economic cooperation in border regions, and the challenges of transnational economic cooperation in border regions.